1997
DOI: 10.1046/j.1469-0705.1997.10020137.x
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of ectopia cordis at 10 weeks of gestation using two‐dimensional and three‐dimensional ultrasonography

Abstract: We report here the earliest prenatal diagnosis to date of a case of ectopia cordis using both two-dimensional and three-dimensional ultrasound at 10 weeks of gestation. Both two-dimensional and three-dimensional ultrasound clearly revealed a thoracoabdominal ectopia cordis and an omphalocele. Histopathological examination confirmed the prenatal ultrasonic findings. In addition to an ectopia cordis, a supraumbilical hepato-omphalocele, absence of a pericardium and an anterior diaphragmatic defect were seen, alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 0 publications
1
33
0
1
Order By: Relevance
“…Liang et al [2] reported a case of ectopia cordis and omphalocele diagnosed in the 10th week of gestation through two-and three-dimensional modes, and the pathological fi ndings were compatible with a Pentalogy of Cantrell variant. Bonilla-Musoles et al [3] evaluated 12 fetuses with defects of closing of the abdominal wall, with one case of Pentalogy of Cantrell, by two-and three-dimensional modes, and observed that although all the defects of closing were diagnosed by the two-dimensional mode, additional information was provided by the three-dimensional ultrasound in all cases.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Liang et al [2] reported a case of ectopia cordis and omphalocele diagnosed in the 10th week of gestation through two-and three-dimensional modes, and the pathological fi ndings were compatible with a Pentalogy of Cantrell variant. Bonilla-Musoles et al [3] evaluated 12 fetuses with defects of closing of the abdominal wall, with one case of Pentalogy of Cantrell, by two-and three-dimensional modes, and observed that although all the defects of closing were diagnosed by the two-dimensional mode, additional information was provided by the three-dimensional ultrasound in all cases.…”
Section: Discussionmentioning
confidence: 97%
“…Th ere are only two reports in the medical literature of the use of three-dimensional ultrasound, and both in the fi rst and second trimester [2,3] . Th ere are no reports in the third trimester.…”
Section: Introductionmentioning
confidence: 99%
“…The pentalogy of Cantrell can be usually diagnosed in the first trimester of pregnancy with antenatal sonogram [7] and should be ruled out in any fetus with omphalocele or ectopia cordis [5]. Moreover, the presence of pericardial effusion on antenatal sonogram should raise suspicion for associated anterior diaphragmatic hernia and diaphragmatic-pericardial defects and hence meticulous search for the features of the pentalogy of Cantrell should be considered [8].…”
Section: Discussionmentioning
confidence: 99%
“…2,3 With prenatal ultrasonography, the pentalogy of Cantrell usually can be diagnosed in the first trimester of pregnancy. 6 In a fetus with omphalocele, pentalogy of Cantrell should be ruled out. If pericardial effusion can be seen, associated anterior diaphragmatic hernia and diaphragmatic pericardial defects may be suspected and specific and detailed search for the features of the pentalogy of Cantrell should be done.…”
Section: Discussionmentioning
confidence: 99%